Bilateral total duplication of clavicle: First reported case - Shaikh, Tanveer; Ansari, Sharique; Mandhane, Nisha; V. U., Thahir; Karandikar, Sangram; Khan, Naseem; Deolekar, Sandesh (International Journal of Research in Medical Sciences, 2017)
A very rare first case of bilateral duplication of the clavicle is presented here. Duplication of the clavicle has been described in only six reports based on a search of the world literature, with single case of bilateral duplication (incomplete) of clavicle being reported. The detection of anatomic anomalies are increasing with the advancement of technology in medicine field. This case is more of academic interest as it is the first case of total bilateral duplication of clavicle.